Current understanding of disease control and its application in patients with chronic rhinosinusitis - Zhou, Jiahui; Yuan, Fan; Huang, Tianhao; Zhu, Li; Wu, Dawei (Frontiers in Cellular and Infection Microbiology, 2023)
Background Disease control is a primary treatment goal for patients with chronic rhinosinusitis (CRS). This study aims to summarize the evaluation parameters of disease control and then identify predictors of poorly controlled CRS. Methods A systematic review of the literature was performed on PubMed, Google Scholar, Scopus, and Cochrane databases to identify studies relating to disease control in CRS. Results The concept of disease control in patients with CRS involved the longitudinal assessment of the disease state and was also an important goal of treatment. As a metric of the disease state, the disease control reflected the ability to keep disease manifestations within certain limits, the efficacy after treatment, and the impact on quality of life. Validated measurements, such as EPOS2012 criteria, EPOS2020 criteria, Sinus Control Test, and patient/physician-reported global level of CRS control, have been utilized in clinical practice. These existing disease control instruments incorporated various disease manifestations and categorized patients into two (well-controlled and poor-controlled), three (uncontrolled, partly controlled, and controlled), or five (not at all, a little, somewhat, very, and completely) control categories. Eosinophilia, high computerized tomography score, bilateral sinonasal disease, asthma, allergic rhinitis, female gender, aspirin intolerance, revision surgery, low serum amyloid A, and specific T cell subtype would predict poorly controlled CRS. Conclusions The concept of disease control and its application were gradually developed in patients with CRS. The existing disease control instruments demonstrated a lack of uniformity regarding the controlled criteria and included parameters.